Search methods for a vision system configuration - Hüsser, Olivier; Hügli, Heinz (My University, 2001)
Flexible production sets new requirements in quality control. Vision systems must be highly versatile to cope with the ever changing production cycles and setup time must be reduced to a minimum so as to reduce downtime. This paper considers an automatic configurator tool that assists the operator during the setup of a visual inspection system and discusses heuristic search methods used to speed up the configuration optimisation process.